KAJIAN PENGARUH GEMPA BUMI MERUSAK DI WILAYAH PROVINSI BENGKULU TERHADAP PLTA MUSI - Asdani Soehaimi (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The PLTA Musi is located in a pull apart basin between Ketahun and Musi - Keruh segments of Sumatera fault zone. The geotechnical subsurface of PLTA Musi is divided into four layers involving basement rock layer 1 with N = 1000, Vs =646 m/second; basement rock layer 2 with N = 500, Vs =521 m/second, and thickness h= 12 - 16 m; soft rock layer 1 with N = 200 and Vs = 392 m/second, thicknes h = 6 - 14 m, soft rock layer 2 with N = 100, Vs = 316 m/second, and thickness  h = 10 - 26 m. The natural period (Ts) between based rock layer 1  and 2 is 0,092 second ≤Ts≤ 0,099 second, for based rock layer  2 and soft rock layer 1is  0,06 second ≤ Ts ≤ 0,1 second, and soft rock layer 1 and 2 is0,12 second ≤ Ts ≤ 0,26 second. The 1979 and 1997 Kepahyang destructive earthquakes have significant influences to  the  PLTA  Musi  with  maximum  ground  accelaration  133,59  gal  and  equivalent  intensity  VII MMI or  VII MSK.Destructive earthquakes of magnitude Ms = 5 will occur at PLTA Musi at recurrent time of 10 years and earthquake of magnitude Ms = 6, Ms = 7 and Ms = 8 at 40 years, 160 years and 630 years.Keywords: The Musi PLTA,destructive earthquake, earthquake hazard and risk